The impact of the COVID-19 pandemic on the mental health of medical students - Ekmekci Ertek, İrem and Özkan, Seçil and Candansayar, Selçuk and İlhan, Mustafa (Journal of Surgery and Medicine, 2022)
Background/Aim: Medical students are at high risk for mental problems with already increased levels of stress and depression. The literature shows that the COVID-19 pandemic has affected the mental health of the population including medical students. However, yet, there is insufficient data to compare the mental health of medical students before and after the pandemic. In this study, it was aimed to investigate the impact of COVID-19 pandemic on medical students’ mental health. Methods: First part of these two cross- sectional studies was conducted in 2019, before the pandemic, and the second one was performed in 2021. A sociodemographic data form, The Center for Epidemiologic Studies Depression Scale (CES-D), Perceived Stress Scale (PSS), and Maslach Burnout Inventory-Student Survey (MBI-SS) were applied to 1306 students in 2019 and 898 students in 2021, from all 6 grades studying at a Turkish medical school. Prevalence of depression, PSS and MBI-SS scale scores were compared in terms of year of the study, grades and some demographic variables. Results: The prevalence of depression was 64.2% in 2019 and increased to 90.9% after the pandemic. Participants with a personal or family history of being COVID-19 (+) had higher scores in CES-D (P=0.002 and P=0.001, respectively) and PSS (P=0.015 and P=0.004, respectively). Regression analysis showed that female gender, studying in preclinical phases, and living alone were significant predictors of CES-D and PSS scores. Conclusion: The COVID-19 pandemic negatively affected the mental health of medical students as well as the entire society. Preventive mental health practices are required for this vulnerable population, especially for groups determined to be at risk.